This bird has flown eaudiobook - Hoffs, Susanna (2023)
This delightfully funny and steamy novel about music, fate, and love from beloved songwriter and Bangles co-founder Susanna Hoffs is "a total knockout" and "the smart, ferocious rock-star redemption romance you didn't know you needed" ( New York Times Book Review). Jane Start is thirty-three, broke, and recently single. Ten years prior, she had a hit song—written by world-famous superstar Jonesy—but Jane hasn't had a breakout since. Now she's living out of four garbage bags at her parents' house, reduced to performing to Karaoke tracks in Las Vegas. Rock bottom . But when her longtime manager Pippa sends Jane to London to regroup, she's seated next to an intriguing stranger on the flight—the other Tom Hardy, an elegantly handsome Oxford professor of literature. Jane is instantly smitten by Tom, and soon, truly inspired. But it's not Jane's past alone that haunts her second chance at stardom, and at love. Is Tom all that he seems? And can Jane emerge from the shadow of Jonesy's earlier hit, and into the light of her own? In turns deeply sexy, riotously funny, and utterly joyful, This Bird Has Flown explores love, passion, and the ghosts of our past, and offers a glimpse inside the music business that could only come from beloved songwriter Susanna Hoffs. "Clever and entertaining . . . with an insider's feel for the mixed blessings of pop fame​." — Los Angeles Times "Part British romcom, part Jane Eyre , and one hundred percent enjoyable." —Tom Perrotta "In this sexy, page-turning treat, Susanna Hoffs writes as engagingly as she sings." —Helen Fielding "This isn't just a book, it's a love song, and it should come as no surprise that Susanna Hoffs has crafted the perfect one to put on your playlist." ―Christina Lauren "A sweet and tender romance—and a valentine to music." —NPR "This book is a blast . . . about art and new beginnings and love and friendship and taking risks, it's such a fun read." ―Jasmine Guillory